Teaching for Justice in a Contradictory World - George Reilly (MDPI AG, 2017)
School today is caught in the dilemma of being expected to educate young people so that they can be integrated into modern industrial society. Because of structural injustices in society, not all students have equal chances in this integration process. Education in school is also expected to impart proficiency in skills which go beyond the functional skills which a productive society needs. These softer skills can threaten the aims of modern society because they have the potential to question its underlying rationale. Young people learn these skills in their everyday lives with their peers outside of school. They form part of the cultural wealth which students bring with them to school. It is up to school to draw on this cultural wealth of students and to foster the various forms of cultural capital contained therein so that students learn not to be victims of a one-sided schooling which reproduces those injustices that pervade modern society by placing excess value on cultural assets which are favored by dominant groups in society.